Development Guidelines for Visionary Leadership of School Administrators Under the Office of Maha Sarakham Primary Educational Service Area 3 - Nasatien, Nasatien; Ruangsuwan , Chayakan (Journal for Developing the Social and Community, 2024)
The objectives of this research were 1) to study the needs about the current and the desired conditions for Visionary Leadership of School Administrators Under the Office of Maha Sarakham Primary Educational Service Area 3 2) To study the guidelines for the development of Visionary Leadership of School Administrators Under the Office of Maha Sarakham Primary Educational Service Area 3. The research was divided into 2 phases. Phase 1 study the current situation. Visionary Leadership of School Administrators Needs From the sample group, 285 were divided into 40 administrators and 245 teachers. Sampling using a stratified random sampling method. The tool was a questionnaire. The Item Objective Congruence Index (IOC) value 0.80–1.00 The present condition had a confidence value of 0.93, a power of discrimination between 0.38 - 0.75 and a desirable condition had a confidence value of 0.94 and a power of discrimination was between 0.36 - 0.74. The statistics used in the research were frequency, percentage, mean, standard deviation and Priority Needs Index. Phase 2 studied the guidelines for the development of Visionary Leadership of School Administrators using the interview forms, interviewed 7 senior experts and using the descriptive analysis. The results of the research were as follows: 1) The current Visionary Leadership of School Administrators in schools. Overall and each aspect is at a moderate level. The desirable condition Visionary Leadership for educational administration in schools as a whole and in each aspect was at the highest level. and the study of the priority needs index to develop Visionary Leadership for educational administration in schools in between PNImodified 0.37 - 0.41 and 2) The guidelines for the development of Visionary Leadership for educational administration in schools. Found 39 approaches, divided into Formulating 11 Approaches. Dissemination 9 Approaches. Implementing 10 Approaches. and Role model 9 Approaches. There is an assessment of the suitability and feasibility overall and in each aspect. At the highest level.